A consensus guideline for antipsychotic drug use for dementia in care homes. Bridging the gap between scientific evidence and clinical practice. (10th June 2015) - Zuidema, Sytse U.; Johansson, Alice; Selbaek, Geir; Murray, Matt; Burns, Alistair; Ballard, Clive; Koopmans, Raymond T. C. M.
ABSTRACT: Background: To produce a practice guideline that includes a set of detailed consensus principles regarding the prescription of antipsychotics (APs) amongst people with dementia living in care homes. Methods: We used a modified Delphi consensus procedure with three rounds, where we actively specified and optimized statements throughout the process, utilizing input from four focus groups, carried out in UK, Norway, and the Netherlands. This was done to identify relevant themes and a set of statement that experts agreed upon using the Research and Development/University of California at Los Angeles (RAND/UCLA) methodology. Results: A total of 72 scientific and clinical experts and 14 consumer experts reached consensus upon 150 statements covering five themes: (1) General prescription stipulations, (2) assessments prior to prescription, (3) care and treatment plan, (4) discontinuation, and (5) long-term treatment. Conclusions: In this practice guideline, novel information was provided about detailed indication and thresholds of symptoms, risk factors, circumstances at which APs should be stopped or tapered, specific criteria for justifying long-term treatment, involvement of the multidisciplinary team, and family caregiver in the process of prescription. The practice guideline is based on formal consensus of clinicians and consumer experts and provides clinicians relevant practical information that is lacking in current guidelines.